Untargeted ¹H NMR metabolomics of Elephantopus scaber reveals correlation with anti-Vibrio activity - Isha, Azizul; Sharifuddin, Noraznita; Abu Zarin, Mazni; Rukayadi, Yaya; Abdull Razis, Ahmad Faizal (Springer, 2025)
Background: Elephantopus scaber (E. scaber) is a medicinal plant frequently used in traditional medicine for its health-promoting properties, as it contains numerous physiologically active compounds. However, scientific research on the metabolite profile of this plant remains limited. Purpose: This study aims to establish chemical profiles of E. scaber leaf extracted by different polarity solvents (hexane, chloroform, acetone and 70% (v/v) ethanol) and to correlate the chemical markers to anti-Vibrio activities using the 1H NMR-metabolomics approach. Methods: A portion of the powdered E. scaber leaf sample was extracted using different solvent systems, namely hexane, chloroform, ethyl acetate, and 70% (v/v) ethanol. Each extract was evaporated to dryness and subsequently lyophilized before being subjected to NMR analysis. For multivariate data analysis, all samples were prepared in six replicates. Results: The application of principal component analysis effectively distinguished the extracts based on their metabolite profiles. Acetone and 70% (v/v) ethanol were determined to have good extraction efficiency. The findings from the partial least squares analysis revealed a significant correlation between the polar chemicals present in the acetone extract of E. scaber leaf and its anti-Vibrio activity. According to the loading plot, acetone extracts contain a more diversified spectrum as compared to the other extracts, with a total of 42 metabolites comprising carbohydrates, amino acids, flavonoids, terpenoids, organic and fatty acids. Conclusion: The identification of these metabolites in E. scaber leaf extracts indicate that they may play a significant role in the anti-Vibrio action.